On the radio-oxidation, at high doses, of an industrial polyesterurethane and its pure resin. (December 2017) - Fromentin, E.; Aymes-Chodur, C.; Doizi, D.; Cornaton, M.; Miserque, F.; Cochin, F.; Ferry, M.
Abstract: The polymers inside the technological waste packages degrade under radio-oxidation. In the context of the geological nuclear waste storage, the long-term behavior of these polymers must be better understood, especially at high doses. The general objective is to ensure the safety of the geological underground repository. In this study, we focus on an industrial polyesterurethane, used as glovebox gloves, and its pure resin. These two materials were radio-oxidized at different high doses. The modifications induced by irradiation using low stopping power ionizing rays were assessed through the study of the gas release, the in-chain modifications, and the formation of oxidation products of low molecular mass. Gas mass spectrometry was used to quantify the gas release with exposure doses up to 4000 kGy for the pure material and 10 000 kGy for the industrial polymer: the evolution with dose is weak and is increasing only in the case of carbon dioxide. The in-chain modifications were identified by infrared spectroscopy or X-ray photoelectron spectroscopy, and correspond probably mainly to the formation of hydroperoxides, hydroxyls and ketones, along with alkenes. By GC-MS or thermodesorption analyses, oxidation products trapped in the polymer matrixes are identified and are esters, carboxylic acids, alcohols, an aromatic molecule and oligomers. Highlights: Aromatic polyesterurethanes radio-oxidization at high doses using gamma-rays. Investigation of the role of fillers and additives on radio-oxidation mechanisms. Instantaneous gas emission rates as a function of dose. Low molecular mass trapped oxidation products identification.